Organocatalytic enantioselective synthesis of 1-vinyl tetrahydroisoquinolines through allenamide activation with chiral Brønsted acids1. Issue 14 (19th February 2015) - Manoni, E.; Gualandi, A.; Mengozzi, L.; Bandini, M.; Cozzi, P. G.
<x xml:space="preserve">Abstract</x> In this paper we present a new approach for the realization of tetrahydroisoquinoline scaffolds via stereoselective proto-activation of suitable allenamide precursors.